Barrett’s Epithelium to Esophageal Adenocarcinoma: Is There a “Point of No Return”? - Panda, Anshuman; Shin, Mi ryung; Cheng, Christina; Bajpai, Manisha (Frontiers in Genetics, 2021)
Background: Esophageal adenocarcinoma (EA) arises from the Barrett’s epithelium (BE) and chronic gastroesophageal reflux disease is considered the strongest risk factor for disease progression. All BE patients undergo acid suppressive therapy, surveillance and BE removal by surgery or endoscopic ablation, yet the incidence of EAC continues to increase. Despite known side effects and mortality, the one-size fits all approach is the standard clinical management as there are no reliable methods for risk-stratification. Methods: Paired end Illumina NextSeq500 RNA sequencing was performed on total RNA extracted from 20 weeks intervals (0W, 20W, 40W, and 60W) of an in-vitro BE carcinogenesis (BEC) model to construct time series global gene expression patterns (GEPs). The cells from two strategic time points (20W and 40W) based on the GEPs were grown for another 20 weeks, with and without further acid and bile stimulation (ABS), and the recurrent neoplastic cell phenotypes were evaluated. Results: Hierarchical clustering of 866 genes with ≥2 fold change in transcript levels across the four time points revealed maximum variation between the BEC20W and BEC40W cells. Enrichment analysis confirmed that the genes altered ≥2 fold during this window period associated with carcinogenesis and malignancy. Intriguingly, the BEC20W cells required further ABS exposure to gain neoplastic changes but the BEC40W cells progressed to malignant transformation after 20 weeks even in the absence of additional ABS. Discussion: The transcriptomic gene expression patterns, in the BEC model demonstrate evidence of a clear threshold in the progression of BE to malignancy. Catastrophic transcriptomic changes during a window period culminate in the commitment of the BE cells to “point of no return” and removal of ABS is not effective in preventing their malignant transformation. Discerning this “point of no return” during BE surveillance by tracking the GEPs has the potential to evaluate risk of BE progression and enable personalized clinical management.